Desain Protokol Keamanan Data Berbasis Blockchain pada Pengolahan Data Pengguna Aplikasi E-commerce - Purba, Risky Pradipa; Wijaya, Bayu Angga; Nazara, Leni Wati; Utami, Sekar Suryati (METIK JURNAL (AKREDITASI SINTA 3), 2025)
Data security is a crucial aspect in developing e-commerce applications, considering the high risk of user data leakage. This study aims to design, implement simulations, and analyze blockchain technology-based security protocols to comprehensively improve protection of user data in e-commerce systems. The methods used include literature studies, system requirements analysis, and protocol architecture design using a smart contract approach on the Ethereum Testnet platform. The results of this study indicate that this protocol design is very effective in the form of a protocol design that supports data integrity, transparency, and authentication through decentralization and cryptography features in the blockchain. Specifically, testing proves 100% success in data encryption using AES-256 and 100% success in recording data hashes using SHA-256 to the blockchain. This design has also been shown to be able to distinguish and reject unauthorized access and record all activities, both on-chain and off-chain, supporting the principle of non-repudation. Operational efficiency is also seen with an average data transaction completion time of 4.2 seconds, indicating that this system is quite responsive for an e-commerce environment. With this approach, the developed protocol significantly minimizes the potential for data manipulation and misuse by irresponsible parties. This simulation implementation clearly demonstrates how blockchain can be adopted in the context of cybersecurity to support higher user trust in e-commerce platforms, as well as ensure data privacy protection through encrypted off-chain storage of data.